Circulating Hematopoietic Progenitor Cells are Decreased in COPD. (1st June 2014) - Janssen, William J.; Yunt, Zulma X.; Muldrow, Alaina; Kearns, Mark T.; Kloepfer, Angela; Barthel, Lea; Bratton, Donna L.; Bowler, Russell P.; Henson, Peter M.
Abstract Rationale: Bone marrow derived progenitor cells participate in the repair of injured vessels. The lungs of individuals with emphysema have reduced alveolar capillary density and increased endothelial apoptosis. We hypothesized that circulating levels of endothelial and hematopoietic progenitor cells would be reduced in this group of patients. Objectives: The goal of this study was to measure circulating levels of endothelial progenitor cells (EPCs) and hematopoietic progenitor cells (HPCs) in subjects with COPD and to determine if progenitor levels correlated with disease severity and the presence of emphysema. Methods: Peripheral blood mononuclear cells were isolated from 61 patients with COPD and 32 control subjects. Levels of EPCs (CD45dim CD34+) and HPCs (CD45+ CD34+ VEGF-R2+) were quantified using multi-parameter flow cytometry. Progenitor cell function was assessed using cell culture assays. All subjects were evaluated with spirometry and CT scanning. Measurements and Main Results: HPC levels were reduced in subjects with COPD compared to controls, whereas circulating EPC levels were similar between the two groups. HPC levels correlated with severity of obstruction and were lowest in subjects with severe emphysema. These associations remained after correction for factors known to affect progenitor cell levels including age, smoking status, the use of statin medications and the presence of coronary artery disease. The ability of mononuclear cells to form endothelial cell colony forming units (EC-CFU) was also reduced in subjects with COPD. Conclusions: HPC levels are reduced in subjects with COPD and correlate with emphysema phenotype and severity of obstruction. Reduction of HPCs may disrupt maintenance of the capillary endothelium, thereby contributing to the pathogenesis of COPD.